What Philosophy of Science has to Offer to Theology - Halvorson, Hans (Philosophy, theology and the sciences, 2023)
In this text, I explore the intertwined relationship between philosophy of science and theology, and the challenges they both encounter in the academic realm. While theology is struggling to maintain its relevance, philosophy of science has gained recognition and offers valuable insights to theologians. I argue that theologians can benefit from engaging with the content and methods of specific sciences, and philosophers of science can help affirm the methodological legitimacy of theology. However, it is important to note that science itself is facing its own set of problems. There is a decline in interest and job satisfaction among scientists, a growing gap between science and the humanities, a crisis of conceptual understanding, and a perceived lack of meaning and purpose. In this context, I propose that theology and philosophy can play a crucial role in addressing these issues. In particular, theology can offer a supportive environment for discussing meaning, values, and the ultimate questions of human existence. Philosophy, on the other hand, can help bridge the gap between science and the humanities, fostering interdisciplinary dialogue and a more holistic understanding of our world.